Nexus between FDI, Infrastructure Investment, Tourism Revenues, and Economic Growth: Mega Event Evidence - Mustafa Mohammad Alalawneh; Jeyhun Mammadov; Ameen Alqasem (Emerging Science Journal, 2021)
The object of this study is to examine the response of economic growth in Germany to 2006 FIFA World Cup hosting (represented by the heavily influenced variables of this huge event: Growth of Infrastructure Spending, Tourism Revenues, and Foreign Direct investment) during the period (2000 – 2017). The study employed Dynamic Ordinary Least Square (DOLS) approach to estimate the long-run equilibrium relationships amongst the variables. The results indicate that there is a co-integrating long-run relationship among the studied variables and provide empirical evidence showing that an increase in the growth of infrastructure spending (GINFR) 1 unit leads to an increase in the growth of GDP (GGDP) by 0.374 unit, an increase in the tourism revenues (TR) 1 unit leads to increase in the growth of GDP (GGDP) by 0.155 unit, and an increase in foreign direct investment (FDI) 1 unit leads to an increase in the growth of GDP (GGDP) by 0.055 unit. What distinguishes this paper is that it is one of the rare studies that went beyond the short effect of mega-events on the host country and investigated the long-term economic impact of the most important macro variables associated with mega-events on economic growth. Doi: 10.28991/esj-2021-01323 Full Text: PDF